2012
DOI: 10.1111/j.1464-410x.2012.11552.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms and depression

Abstract: What ' s known on the subject? and What does the study add? Depression plays an important role in pathogenesis of BPH. Our study shows that prostatic symptoms can be helpful in the screening for depression. OBJECTIVE• To evaluate the relationship between lower urinary tract symptoms (LUTS) and depression in men through validated questionnaires. PATIENTS AND METHODS• Healthy male workers ( n = 673) were invited to a free health check-up.• Patients underwent a detailed medical examination.• All participants comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 20 publications
2
38
1
4
Order By: Relevance
“…In line with previous studies, more severe LUTS symptoms were associated with more severe depressive (Felde et al, 2012;Rom, Schatzl, Swietek, Rucklinger, & Kratzik, 2012;Wong, Woo, Leung, & Leung, 2010) and anxiety symptoms (Felde et al, 2012). The result of regression analysis found that the higher IPSS score of urgency was associated with higher anxiety scores in females.…”
Section: Psychology Health and Medicine 11supporting
confidence: 89%
“…In line with previous studies, more severe LUTS symptoms were associated with more severe depressive (Felde et al, 2012;Rom, Schatzl, Swietek, Rucklinger, & Kratzik, 2012;Wong, Woo, Leung, & Leung, 2010) and anxiety symptoms (Felde et al, 2012). The result of regression analysis found that the higher IPSS score of urgency was associated with higher anxiety scores in females.…”
Section: Psychology Health and Medicine 11supporting
confidence: 89%
“…Meanwhile, it was found that the clinical manifestation of LUTS/BPH is strongly associated with psychiatric disturbances such as depression, anxiety, and stress vulnerability, and impairments of instrumental activities during daily living in some studies (5, 10, 11, 12, 13, 14, 15, 16, 17). For instance, the recent large cohort study (14) have also demonstrated the important relationship between LUTS/BPH and depression, in which depression was significantly associated with the severity of the diseases as well as it also involves in all stages of LUTS.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the recent large cohort study (14) have also demonstrated the important relationship between LUTS/BPH and depression, in which depression was significantly associated with the severity of the diseases as well as it also involves in all stages of LUTS. According to a large observational, longitudinal, multicenter study (n=666), a substantial proportion (22.6%) of LUTS/BPH patients reported anxiety or depression and they also explained a 7% of variance for explaining the severity of LUTS/BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that men with moderate to severe LUTS had poorer role functioning, had less energy, and had more depressed and anxious feelings . Furthermore, Rom et al investigated the relationship between LUTS and depression in 673 elderly men through validated questionnaires, and found that LUTS were significantly associated with depression . Disregarding men with LOH or usual elderly people, LUTS may be associated with psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%